Upaya Peningkatan Kualitas Lingkungan Hidup di Kota Yogyakarta - Salsabila Afra Safitri; Najla Hikmalia Dhiyaa Ulhaq; Salim, Agus (Jurnal Ilmu Sosial dan Humaniora, 2024)
The purpose of this study is to compare Yogyakarta's environmental quality index in 2023 with the environmental quality index in 2022. The study identified the parties responsible for the local environmental sector as well as the causes and solutions to problems related to air and water pollution. This was measured using a qualitative approach in this study, with the components of the Water Quality Index (WQI), Air Quality Index (AQI), and Environmental Quality Index (EQI) covered in the literature review. The conclusion of this study shows that the environmental quality index of Yogyakarta City still needs improvement to increase the quality of the environment to a better and more sustainable level.